2022
DOI: 10.2174/0929867329666220727120646
|View full text |Cite
|
Sign up to set email alerts
|

Oxytocin: An Old Hormone, a Novel Psychotropic Drug and its Possible Use in Treating Psychiatric Disorders

Abstract: Background: Oxytocin is a nonapeptide synthesized in the paraventricular and supraoptic nuclei of the hypothalamus. Historically, this molecule has been involved as a key factor in the formation of infant attachment, maternal behavior and pair bonding and, more generally, in linking social signals with cognition, behaviors and reward. In the last decades, the whole oxytocin system has gained a growing interest as it was proposed to be implicated in etiopathogenesis of several neurodevelopmental and neuropsychi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 715 publications
0
7
0
Order By: Relevance
“…Oxytocin secreted by the hypothalamus can regulate social behavior ( 26 , 27 ). To determine whether ZIKV infection affects oxytocin production, we used immunostaining for oxytocin.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Oxytocin secreted by the hypothalamus can regulate social behavior ( 26 , 27 ). To determine whether ZIKV infection affects oxytocin production, we used immunostaining for oxytocin.…”
Section: Resultsmentioning
confidence: 99%
“…In this study, we detected the presence of ZIKV in the hypothalamus, which was consistent with our previous study ( 18 , 37 ). As the center of the neuroendocrine system, the hypothalamus can release hormones to regulate various important physiological processes, such as GnRH regulating reproductive development via the HPG axis ( 38 ) and oxytocin regulating social behaviors ( 26 , 27 ). Both GnRH and oxytocin secreted by the hypothalamus were significantly reduced in ZIKV-infected mice, which was highly correlated with persistent damage of ZIKV infection.…”
Section: Discussionmentioning
confidence: 99%
“…One treatment option that has been investigated to address psychiatric difficulties is the administration of oxytocin [24]. Oxytocin is a bonding hormone that has an important role in linking social signals with cognitions and behaviours [25]. Research has indicated that an intranasal oxytocin administration improved emotion recognition and/or state anxiety in healthy individuals [26][27][28][29]; and in individuals with social cognitive deficits including autism [30], social anxiety [31], schizophrenia [32] and eating disorders [33,34].…”
Section: Intranasal Oxytocin To Improve Emotion Recognition and Trustmentioning
confidence: 99%
“…As reviewed above, the drugs used in PTSD are mainly symptomatic or derived from limited biological abnormalities reported in the patients; this clearly reflects the lack of comprehensive knowledge of the pathophysiology of the disorder. Indeed, current research suggests that PTSD may result from impairments in fear extinction, an increase in generalized anxiety, and a negative bias toward perceiving threats from neutral inputs and feeling danger in secure settings that are also thought to be due to different neurochemical abnormalities [ 12 , 15 , 42 , 43 , 44 , 45 ]. In any case, the mechanisms underlying these altered processes are not totally understood.…”
Section: Novel Pharmacological Targets In Ptsdmentioning
confidence: 99%
“…Oxytocin (OT) is a pleiotropic hormone produced in the paraventricular and supraoptic nuclei of the hypothalamus and released into the bloodstream through the posterior pituitary gland and into the brain through several pathways [ 99 ]. Oxytocin seems to promote social interactions between conspecifics, attachment, and pair-bonding, and it also exhibits anti-inflammatory properties as a powerful immune and stress system modulator, beyond its “classical” activities, such as uterine contractions during labor and milk production [ 45 , 101 , 102 ] ( Figure 3 ).…”
Section: Novel Pharmacological Targets In Ptsdmentioning
confidence: 99%